Structures and differences of the cognitive abilities of top handball, volleyball, basketball and soccer players - Ilic, I. (Facta Universitatis: Series Physical Education and Sport, 2015)
In modern sport, cognitive abilities are one of the key factors that affect the success rate of athletes. The goal of this study is to determine the statistically significant structures and differences in the area of cognitive abilities on the sample of top handball, volleyball, basketball and football players. The sample of subjects consisted of 200 male athletes, divided into four groups of 50 subjects. In order to assess the conative characteristics of the subjects, KOG 3 battery of tests was used. The structures and the differences of the athletes` test results were determined using the method of principal component analysis and canonical discriminant analysis. The observed structure of cognitive abilities indicate the existence of a single, general factor. The results of all applied tests are significant at the entire sample level, most dominantly on the input processor level, followed by serial and parallel processor test values, which can be attributed to the requirements imposed by the top rank of the competition in which participants perform. The differences in cognitive characteristics exhibited the isolation of one discriminant dimension. The values shown in the structure matrix suggests that the first discriminative function positively distinguishes the basketball and volleyball players compared to other athletes based on the tests for assessing the efficiency of input and parallel processors. These results can be linked to the fact that volleyball and basketball are more dynamic sports, as well as that specific nature of these sports requires solving of complex tactical tasks.